2014
DOI: 10.12691/wjar-2-2-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Traditional and Improved Granaries in Protecting Maize from <i>Prostephanus truncatus</i> in Small Holder Farming Storage System in Makonde District, Zimbabwe

Abstract: The study was carried out in Makonde District, located 17°21' S and 30°12' E in Mashonaland West Province to assess the efficiency of improved and traditional granaries in protecting traditional and hybrid maize from Prostephanus truncatus. Ten farmers were randomly selected from 20 wards in the District. Multistage cluster sampling and purposive sampling techniques were used. Amongst the 10 selected farmers, 5 were using traditional granaries and the other 5 were using improved granaries. Four farmers used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…These results thus corroborate those that have reported relatively low usage of modern granaries (e.g. Admire and Tinashe (2014) in Zimbabwe, and Midega et al, 2016 in Kenya) with traditional granaries being more commonly used to store maize in most of rural Africa since modern granaries are perceived to be expensive and unaffordable for most of smallholder farmers.…”
Section: Discussionsupporting
confidence: 89%
“…These results thus corroborate those that have reported relatively low usage of modern granaries (e.g. Admire and Tinashe (2014) in Zimbabwe, and Midega et al, 2016 in Kenya) with traditional granaries being more commonly used to store maize in most of rural Africa since modern granaries are perceived to be expensive and unaffordable for most of smallholder farmers.…”
Section: Discussionsupporting
confidence: 89%
“…(Tweheyo 2018:31) It is reported that in Senegal traditional clay granaries have proved to be effective based on the knowledge that nonwinnowed maize stored in a granary takes long to be infested with insects (Gueye et al 2013). Admire and Tinashe (2014) point out that insect pests cause 30% of the post-harvest losses of grains in sub-Saharan Africa because of poor storage systems. According to Tweheyo (2018:31), 'storage can play a significant role in influencing small scale farmers' decisions about the diversity of crops and varieties they adopt and maintain'.…”
Section: Indigenous Knowledge Used In Increasing Food Securitymentioning
confidence: 99%
“…IKS thus forms the basis of the local knowledge that many rural and indigenous people use in their daily lives, and which often influences their decision-making. Admire and Tinashe [2] reported that the development of IKS within the context of livelihoods and natural resources has supported the survival of the indigenous people who have created these systems. Jiri et al [26] noted that IKS is preserved within communities' memories and actions and is often represented through storytelling, music, mythology, idiomatic expressions, festivals, cultural norms, convictions, ceremonies, social regulations, local languages, farming methods, plant species and even in the domestication of animals.…”
Section: Introductionmentioning
confidence: 99%